2024
DOI: 10.3390/foods13071044
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Untapped Potential of Pine Nut Skin By-Products: A Holistic Characterization and Recycling Approach

Agata Nolasco,
Jonathan Squillante,
Salvatore Velotto
et al.

Abstract: The increasing population, food demand, waste management concerns, and the search for sustainable alternatives to plastic polymers have led researchers to explore the potential of waste materials. This study focused on a waste of pine nut processing referred to in this paper as pine nut skin. For the first time, its nutritional profile, potential bioactive peptide, contaminants, and morphological structure were assessed. Pine nut skin was composed mainly of carbohydrates (56.2%) and fiber (27.5%). The fat (9.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…The growing demand for coffee consumption will generate CS, which may cause a serious impact on the environment. Previous studies have reported the way to deal with several wastes from different sectors, such as blueberry by-products, pine nut skin, sea bass by-products, and plant by-products from banana harvesting [25][26][27][28]. After valorization, valuable compounds are obtained and can be applied in food applications.…”
Section: Discussionmentioning
confidence: 99%
“…The growing demand for coffee consumption will generate CS, which may cause a serious impact on the environment. Previous studies have reported the way to deal with several wastes from different sectors, such as blueberry by-products, pine nut skin, sea bass by-products, and plant by-products from banana harvesting [25][26][27][28]. After valorization, valuable compounds are obtained and can be applied in food applications.…”
Section: Discussionmentioning
confidence: 99%